Tigecycline Use in Neonates: 5-Year Experience of a Tertiary Center - İpek, Mehmet Sah; Gunel, Mehmet Emin; Ozbek, Erdal (Journal of Pediatric Infectious Diseases, 2019)
The off-label use of tigecycline to treat serious infections has been reported in pediatric patients. We report four newborn infants diagnosed with sepsis caused by extensively drug-resistant Klebsiella pneumoniae and successfully treated with tigecycline. If no alternative drugs are available, tigecycline may be considered as an option for nosocomial infections even in newborn infants. However, further reports are needed to establish its efficacy and safety.
Keywords: tigecycline; neonate; infection; thrombocytopenia